INSTITUTE OF PUBLIC CONTROL: THEORETICAL-LEGAL ASPECTS - Макеєва, Олена Миколаївна; Коваль, Іванна Олегівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: to find out the genesis and the essence of the Institute of Public Control and its role in development of civil society. Research methods: method of analysis and synthesis, philosophical methods, historical and legal, comparative, logical-semantic and others. Results: in this paper concept and principles of public control are defined, its aspects and subjects are given. Discussion: public control is very important institute of civil society that can protect and implement rights, freedoms and legitimate interests of citizens. Relevance of the Institute of Public Control research dependent on an active role of the public sector in the conditions of becoming a democratic society, the development of European integration processes and the formation of an open information and legal space. Effective dialogue between citizens and public authorities in the form of public control is the key to the democracy. Modern reforms of public authorities should be implemented with the participation of the public, which gives the problem of the Institute of Public Control research topicality and it is needed to find out its essence and significance in the conditions of civil society. The purpose of this paper is to study the theoretical and legal foundations of the Institute of Public Control, its role in the formation and development of civil society. Todays understanding of public control was formed during the long evolution of the views of scientists, which reflected changes in social relations in the state. The origins of the public control is a prerequisite for understanding its contemporary meaning. In broadly and narrowly meanings public control is an institution of civil society. Broadly speaking, it is a checking of the activity of the state for compliance with its declared tasks, adjustment of this activity, subordination of the state policy to the interests of civil society. In a narrow sense, it is a type of social control over the supervision, inspection and evaluation of the activities of public control entities in order to determine the compliance of the functioning of public authorities and local self-government with the requirements of international and national legislation and the interests of citizens. The principals of the public control are rule of law, legality, equality; openness, transparency, reconciliation of interests; publicity; mutual responsibility. Subjects of public control are public bodies of self-organization, mass media, public, trade-union, creative organizations and other public associations, citizens. The introduction of public control should be implemented through the development of its legal basis, in particular, the adoption of the Law of Ukraine «About Public Control» and amending the current legislation of Ukraine.